2018
DOI: 10.1111/1365-2745.13009
|View full text |Cite
|
Sign up to set email alerts
|

Is there a disease‐free halo at species range limits? The codistribution of anther‐smut disease and its host species

Abstract: While disease is widely recognized as affecting host population size, it has rarely been considered to play a role in determining host range limits. Many diseases may not be able to persist near the range limit if host population density falls below the critical threshold level for pathogen invasion. However, in vector‐ and sexually transmitted diseases, pathogen transmission may be largely independent of host density and theory demonstrates that diseases with frequency‐dependent transmission may persist in sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 65 publications
2
45
2
Order By: Relevance
“…These surveys were part of an ongoing project to map host and pathogen distribution with respect to range margins (Bruns et al. ). Populations were surveyed every 50 m in elevation along 13 transects in the Maritime Alps (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These surveys were part of an ongoing project to map host and pathogen distribution with respect to range margins (Bruns et al. ). Populations were surveyed every 50 m in elevation along 13 transects in the Maritime Alps (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if there is a positive correlation between disease prevalence and female frequency, we surveyed D. pavonius populations throughout the broader Maritime Alps region. These surveys were part of an ongoing project to map host and pathogen distribution with respect to range margins (Bruns et al 2018). Populations were surveyed every 50 m in elevation along 13 transects in the Maritime Alps (Fig.…”
Section: Spatial Variation In Sex Ratio and Diseasementioning
confidence: 99%
“…Moreover, a search of two localities in Germany where the disease had been recorded within the past 10 years failed to find the disease, suggesting the disease is not self‐sustaining. Nor was the disease ever found on S. baccifera in the southern Piemonte region of Italy which was a focal area for the present study of the distribution of anther smut and where the disease has previously been found on over 20 other species (Bruns et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, the typical proportions of disease within host populations are between 0.10 and 0.30 for S. latifolia (Antonovics, ), ca. 0.30 for S. vuglaris in upper elevations (Abbate & Antonovics, ), or even >0.50 for Dianthus furcatus or Dianthus pavonius (Bruns et al, ). Therefore, the potential for frequent contact between Microbotryum species on separate host species is high.…”
Section: Methodsmentioning
confidence: 99%
“…Anther‐smut disease, caused by fungi in the genus Microbotryum , is one of the most studied host–pathogen associations in natural systems (Figure ). This disease has been used as a model for pathogen speciation, pollinator‐mediated dispersal, multiple infection, biological invasion, and competition (Abbate & Antonovics, ; Bruns, Antonovics, & Hood, ; Fontaine, Gladieux, Hood, & Giraud, ; Giraud, Gladieux, & Gavrilets, ; Gold, Giraud, & Hood, ; Kemler et al, ; Le Gac, Hood, Fournier, & Giraud, ; Vercken et al, ). Research has shown that the fungi formerly grouped under the Microbotryum violaceum epithet represent a large species complex, consisting of many independent lineages, each specific (i.e., endemic) to only one or a very small number of host species (Kemler et al, ; Le Gac et al, ; Lutz et al, ; Piątek, Lutz, & Kemler, ; de Vienne, Hood, & Giraud, ).…”
Section: Introductionmentioning
confidence: 99%